FENOLOGI DAN PERTUMBUHAN TANAMAN STRAWBERRY DI DATARAN RENDAH SEBAGAI KAJIAN AWAL DAMPAK PERUBAHAN IKLIM TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN - Timotiwu, Paul B; Manik, Tumiar Katarina; Agustiansyah, Agustiansyah; Pramono, Eko (Universitas Lampung, 2021)
Climate change has been understood from air temperature that constantly rising.Â Therefore, to study the impact of climate change on crops growth and production should begin with study the impact of air temperature on crops, so that the technique of making crops adapt to the climate change could be developed.Â Crops reaction on temperature change could be detected from the phenology and quantified with the Growing degree days (GDD). The objective of this research was to identify the impact of temperature change on strawberry phenology and production through cultivating on low land area and calculating the GDD at the end of the planting period.Â The results showed that Strawberry on low land experienced some difficulties to grow in optimal rate; up to the 10th week plant still did not reach the generative state uniformly and canopy coverage was below 20 percent.